IMPLEMENTASI KEBIJAKAN GERAKAN LITERASI SEKOLAH DI SMP NEGERI 3 MALANG - Zubaidah, Siti Hanik; Zuriah, Nurul (Jurnal Kebijakan dan Pengembangan Pendidikan, 2018)
Abstract: This study aims to determine the form of GLS implementation in SMPN 3 Malang, supporting factors, obstacles, and solutions. The study uses a qualitative approach with descriptive methods. Data collection uses interviews, observation, and documentary study techniques. Data analysis with data reduction, data display, and verification. Test the validity of the data by triangulation. The results showed that based on Permendikbud No. 23 of 2015, SMPN 3 Malang made a derivative policy on GLS. Form of GLS implementation in the form of habituation, development, and learning. Literacy is 45 minutes every day as an extracurricular and 30 minutes according to the curricular schedule. The implementation of the three stages of GLS was 84.33% and 92.40% showed the literate school ecosystem. Successful implementation is influenced by clear and consistent communication factors, sufficient resources, disposition with receptive responses, and complete bureaucratic structure with clear SOPs. Internal supporting factors are the active role of school principals and staff, libraries, intakes, and the amount of literacy time. The external factor is the role of the guardians of students in infrastructure. Internal inhibiting factors are the lack of school funds and journal check personnel as well as book rotation, the absence of follow-up literacy activities at home, and internal factors of students (gadget influence). The external inhibiting factor is the absence of the government's role in the budget, training, assistance, monitoring, and evaluation. The solution is to increase cooperation with parents and a new policy as an improvement.Keywords: Policy Implementation, Education, GLSAbstrak: Penelitian ini bertujuan untuk mengetahui bentuk implementasi GLS di SMPN 3 Malang, faktor pendukung, penghambat, dan solusinya. Penelitian menggunakan pendekatan kualitatif dengan metode deskriptif. Pengumpulan data menggunakan teknik wawancara, observasi, dan studi dokumenter. Analisis data dengan data reduction, data dislpay, dan verification. Uji keabsahan data dengan triangulasi. Hasil penelitian menunjukkan bahwa berdasarkan Permendikbud No. 23 Tahun 2015, SMPN 3 Malang membuat kebijakan derivat tentang GLS. Bentuk implementasi GLS berupa pembiasaan, pengembangan, dan pembelajaran. Pelaksanaan literasi adalah 45 menit setiap hari sebagai intrakurikuler dan 30 menit sesuai jadwal kokurikuler. Keterlaksanaan tiga tahap GLS sebesar 84,33 % dan 92,40 % menunjukkan sebagai ekosistem sekolah literat. Keberhasilan implementasi dipengaruhi oleh faktor komunikasi yang jelas dan konsisten, sumber daya yang cukup, disposisi dengan respon menerima, dan struktur birokrasi yang utuh dengan SOP yang jelas. Faktor internal pendukungnya adalah peran aktif kepala sekolah dan staff, perpustakaan, intake, dan banyaknya waktu literasi. Faktor eksternalnya adalah peran wali murid dalam sarana prasarana. Faktor internal penghambatnya adalah minimnya dana sekolah dan tenaga pengecekan jurnal serta perotasian buku, belum adanya tindak lanjut kegiatan literasi di rumah, dan faktor internal peserta didik (pengaruh gadget). Faktor eksternal penghambatnya adalah tidak adanya peran pemerintah terkait anggaran, pelatihan, pendampingan, monitoring, dan evaluasi. Solusinya adalah meningkatkan kerjasama dengan orang tua serta adanya kebijakan baru sebagai penyempurnaan. Kata kunci: Implementasi Kebijakan, Pendidikan, GLS